Penerapan Fungsi Manajemen Pengelolaan Kelas dalam Meningkatkan Minat Belajar Siswa di Era Gen Z - Nurul Azizah; Askari Zakariah; Novita Novita (STIKes Ibnu Sina Ajibarang, 2023)
The aim of this research is to find out about the contribution of educational psychology to curriculum development, as well as its contribution to student development. The research method used in this research is a descriptive literature study. In the Gen Z education era, students' interest in learning is the main focus in implementing classroom management functions. Several internal and external factors influence this interest in learning. Internal factors include curriculum, teaching methods, technology, and the quality of teacher-student relationships, while external factors include the influence of social media, family pressure, and the surrounding environment. Gen Z students are more responsive to flexible and interactive learning, with an emphasis on appropriate modern technology. A curriculum that gives students freedom to study topics of interest or adjust study time to their activities is very important. The use of variations in teaching methods, such as varied presentations and using multimedia, can maintain students' interest in learning. Even though technology provides access to broad information and interactive learning, excessive use can disrupt the learning process, so it needs to be managed in a balanced manner. Positive relationships between teachers and students are a key factor in increasing interest in learning, enabling appropriate and interesting learning arrangements. Social media can be a major distraction and its wise use is necessary to maintain student focus. Pressure from the family can also influence students' interest in learning, so a supportive environment must be created by the teacher. A deep understanding of students' surroundings allows teachers to design classroom management strategies that are more relevant and interesting, involving collaboration between schools, families and communities.